Literary paternity, literary friendship : essays in honor of Stanley Corngold - Corngold, Stanley; Richter, Gerhard, 1967- (University of North Carolina studies in the Germanic languages and literatures ;, 2002)
The 21 essays in this volume offer a reconsideration of modern forms of paternity and friendship as they emerge in works by German writers and philosophers from the 18th through to the 20th century. Writings considered include work by Goethe, Schiller, Kleist, Kafka and Arendt.